2022
DOI: 10.1029/2022gc010606
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Geodynamics Insights From a Machine Learning Approach

Abstract: Thousands of oceanic basalts have been analyzed in the last six decades, building up a large database of Sr, Nd, Hf, and Pb isotope ratios. A characteristic feature of these data is that they are not randomly distributed. In 2D and 3D isotope ratio diagrams, the isotopic variation of oceanic basalts on a local scale, that is, for basalts from one ocean island or ridge segment, is often in form of approximately linear data trends. Combining the local data into a large global data set does not have a randomizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 382 publications
2
18
0
Order By: Relevance
“…Our results help reveal the significant contribution of the deep mantle to large-scale MOR geophysical signals and suggest distinct inter-basin and even sub-basin deep mantle variations. The cluster analysis of ridge isotope geochemistry in Stracke et al (2022) highlighted similar spatial mantle compositional variations. These two results together reinforce the idea that the mantle is recording the integrated tectonic and convective history of the last few hundred million years, leading to inter-basin and sub-basin temperature and isotopic variations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our results help reveal the significant contribution of the deep mantle to large-scale MOR geophysical signals and suggest distinct inter-basin and even sub-basin deep mantle variations. The cluster analysis of ridge isotope geochemistry in Stracke et al (2022) highlighted similar spatial mantle compositional variations. These two results together reinforce the idea that the mantle is recording the integrated tectonic and convective history of the last few hundred million years, leading to inter-basin and sub-basin temperature and isotopic variations.…”
Section: Discussionmentioning
confidence: 78%
“…These patterns may be further analyzed with respect to the tectonic and convective history and aid our understanding of whether the variations in the ridge system originated from the deep mantle versus shallow processes. Thematically, our work is a counterpart to the recent study by Stracke et al (2022), who used non-linear dimension reduction and clustering analysis on multiple isotopic data for global MORBs and Ocean Island Basalts. They showed that ridges and hotspots potentially sample distinct sub-basin-scale isotopic heterogeneities, thus highlighting the role of deep mantle processes in controlling ridge composition.…”
Section: Introductionmentioning
confidence: 99%
“… Pb isotope variation diagrams. (a) 206 Pb/ 204 Pb versus 207 Pb/ 204 Pb and (b) 206 Pb/ 204 Pb versus 208 Pb/ 204 Pb diagrams showing data for Bukken Fiord samples compared to Arctic MORB (including Gakkel Ridge; Stracke et al., 2022a, 2022b), Icelandic OIB (Stracke et al., 2022a, 2022b), basalts from the Chukchi Borderland (Mukasa et al., 2020), and average UCC (Millot et al., 2004). Also shown are various mantle end‐members (after Jackson and Dasgupta, 2008) and the Northern Hemisphere Reference Line (NHRL; after Hart, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…121-122 Ma (Midtkandal et al, 2016;Olierook et al, 2019). The timing of the HALIP may point to a role for this arctic-wide LIP in disturbing the carbon cycle and climate system in the Early Cretaceous (e.g., et al, 2022a, 2022b), Icelandic OIB (Stracke et al, 2022a(Stracke et al, , 2022b, basalts from the Chukchi Borderland (Mukasa et al, 2020), and average UCC (Millot et al, 2004). Also shown are various mantle end-members (after Jackson and Dasgupta, 2008) and the Northern Hemisphere Reference Line (NHRL; after Hart, 1984).…”
Section: Wider Implicationsmentioning
confidence: 99%
See 1 more Smart Citation